Pengaruh Budaya Organisasi, Motivasi, dan Kepemimpinan Terhadap Kinerja Pegawai pada Dinas Komunikasi dan Informatika Kabupaten Kotawaringin Timur - Syamsuri Syamsuri; Marina Gati Endah Mumpuni; Indah Nur Oktavia (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This study aims to determine and analyze the influence of organizational culture, motivation, and leadership on employee performance, both partially and simultaneously. This research is a type of quantitative explanatory research by taking data directly from respondents totaling 24 employees with a census sampling technique using a questionnaire. This means that all respondents in the unit of analysis are used as research samples. From the results of the study by measuring variables using a Likert Scale with Multiple Regression Analysis Techniques after passing the instrument test (validity and reliability test), the classic assumption test and hypothesis testing using SPSS version 25.0, showed that partially or simultaneously, variables of organizational culture, motivation, and leadership a positive and significant effect on employee performance at the Office of Communication and Information of East Kotawaringin Regency. From this study, it can also be suggested that through increasing understanding of organizational culture, work motivation and good leadership will have a real impact on improving employee performance and will determine the success of achieving organizational goals going forward.